Cost Allocation and External Acquisition of Services When Self-Services Exist. - Chen, Joyce T. (The Accounting Review, 1983)
ABSTRACT: This paper demonstrates that the treatment of self-services, their inclusion or exclusion, affects neither the decision relevance of the information made available by the reciprocal method of cost allocation nor the internal versus external acquisition decision made through the underlying technology matrix. Three propositions and proofs are provided, showing that there is a one-to-one transformation between the two treatments of self-services in each of the analyses.